Field notes and letter from Barbara L. Wilson to Thomas H. Kent regarding spring bird sightings, June 1, 1983 - Wilson, Barbara L.et al (1983)
Spring report of birds found in western Iowa contributed by Barbara L. Wilson, June 1, 1983. A letter from Wilson to Thomas H. Kent regarding the spring weather and the effect on bird populations is also included. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed/flatbed